Asymmetric Hydrophosphinylation of Alkynes: Facile Access to Axially Chiral Styrene‐Phosphines. (13th December 2022) - Cai, Baohua; Cui, Yuan; Zhou, Jian; Wang, Yong‐Bin; Yang, Limin; Tan, Bin; Wang, Jun (Joelle)
Abstract: A Cu/CPA co‐catalytic system has been developed for achieving the direct hydrophosphinylation of alkynes with phosphine oxides in delivering novel axially chiral phosphorus‐containing alkenes in high yields and excellent enantioselectivities (up to 99 % yield and 99 % ee). DFT calculations were performed to elucidate the reaction pathway and the origin of enantiocontrol. This streamlined and modular methodology establishes a new platform for the design and application of new axially chiral styrene‐phosphine ligands. Abstract : Through a newly developed Cu/CPA co‐catalytic system, the direct hydrophosphinylation of alkynes with nucleophilic phosphine oxides was achieved to access novel axially chiral phosphorus‐containing alkenes in high yields and excellent enantioselectivities (up to 99 % yield and 99 % ee). DFT calculations were performed to elucidate the reaction pathway and the enantiocontrol model.